THE EFFECT OF SUPPLY CHAIN DRIVERS ON PRODUCTION PERFORMANCE IN THE INDONESIAN FOOD AND BEVARAGE MANUFACTURING INDUSTRY - Ongkowijoyo, Gracia (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
The food and beverage industry is a major contributor to the Indonesian economy, and the Covid-19 epidemic heavily influenced its supply chain sustainability. The purpose of this study is to examine the effect of innovation and demand optimization on partnerships in production and production performance in the food and beverage manufacturing industry in Indonesia. This research is a quantitative study using PLS-SEM. Data collection in this study was carried out by distributing questionnaires with a sample of 54 respondents of owners and managers working in the medium-large food and beverage manufacturing companies in Indonesia. The findings indicate that innovation and demand optimization can encourage companies to do partnerships in production. Innovation and demand optimization also shown to improve company’s production performance. However, there is no significant effect between partnerships in production and production performance. This is because partnerships often experience a dilemma due to the influence on company performance which may either be favorable or unfavorable to the production performance. The research findings extend literature of supply chain management in the context of internal perspectives of the companies. The context of the research is limited to small numbers of medium-large companies in Indonesia, thus, call for further examination with a larger sample size and in different contexts for further finding generalization. This research provides broader view on the internal perspectives of company’s supply chain management through the perspective of Resource Based View, as well as providing several suggestions for managers of medium-large food and beverage manufacturing companies in developing countries.Abstrak dalam Bahasa Indonesia. Industri makanan dan minuman merupakan kontributor utama perekonomian Indonesia, dan pandemi Covid-19 sangat mempengaruhi keberlanjutan rantai pasokannya. Tujuan dari penelitian ini adalah untuk menguji pengaruh inovasi dan optimalisasi permintaan terhadap kemitraan produksi dan kinerja produksi pada industri manufaktur makanan dan minuman di Indonesia. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan PLS-SEM. Pengumpulan data pada penelitian ini dilakukan dengan menyebarkan kuesioner dengan sampel sebanyak 54 responden pemilik dan manajer yang bekerja pada perusahaan manufaktur makanan dan minuman menengah-besar di Indonesia. Temuan menunjukkan bahwa inovasi dan optimalisasi permintaan dapat mendorong perusahaan untuk melakukan kemitraan dalam produksi. Inovasi dan optimalisasi permintaan juga terbukti meningkatkan kinerja produksi perusahaan. Namun, kemitraan produksi tidak berpengaruh signifikan terhadap kinerja produksi. Hal ini disebabkan karena kemitraan produksi seringkali mengalami dilema apakah bisa menguntungkan atau merugikan terhadap kinerja produksi. Temuan penelitian ini memperluas literatur manajemen rantai pasokan dalam konteks perspektif internal perusahaan. Konteks penelitian ini terbatas pada sejumlah kecil perusahaan menengah-besar di Indonesia, sehingga memerlukan penelitian lebih lanjut dengan jumlah sampel yang lebih besar dan dalam konteks yang berbeda untuk meningkatkan generalisasi temuan penelitian. Penelitian ini memberikan pandangan yang lebih luas mengenai perspektif internal manajemen rantai pasok perusahaan melalui perspektif Resource Based View, serta memberikan beberapa saran bagi para manajer perusahaan manufaktur makanan dan minuman menengah-besar di negara berkembang